IMPACTS OF ORGANIZATI ONAL EARNI NG CAPABILITY AND ISO 9001 EFFECTIVENESS ON FI NANCIAL PERFORMANCE OF EXPORTING COMPANIES IN THE FEDERATION OF BOSNIA AND HERZEGOVINA - Ensar Mekić; M. Sait Dinç (Economic Review)
The main purpose of this study was to investigate the relationship between Organizational Learning Capability, ISO 9001 Effectiveness and Financial Performance f Bosnian exporters. Based on literature review, a conceptual model was validated and the hypotheses were proposed. The measurement instrument used in this study is a structured survey prepared based on literature review. The target population were the managers of Bosnian exporters that have the ISO 9001 standard implemented in the company. In total, 84 surveys were completed by respondents, which is sample good enough for the entity of the Federation of Bosnia and Herzegovina. Before conducting a regression analysis in Software Package for Social Sciences, the exploratory factor analysis was conducted and five items were extracted. The regression results indicated a strong and positive influence of ISO 9001 Effectiveness on Financial Performance and Organizational Learning Capability of Bosnian exporters. A positive relationship of Organizational Learning Capability and Financial Performance was not confimed.